Art and Nihilism A 20th Century Cultural View - Sanchez, Quintana Esteban (International Journal of Multidisciplinary Applied and Science Research, 2024)
In this text we will deal with some nuances of the relationship between nihilism and art in the context of the cultural crisis of the early twentieth century. To carry out this task, the following approach is proposed: first, some generalities of nihilism are established. Second, the perspective of Nietzsche is outlined, he is the one who detects that the cause of the devaluation of values has its origin in the Platonist tradition of the Western thought, proposing that, in order to overcome this situation, it is necessary to transvalue values towards a new direction. Next, we seek to reflect how nihilism took over as a crisis of civilization at the beginning of the twentieth century, to do this we will review some perspectives of artists and men of letters who developed their work in this era. Finally, a conclusion is proposed